What is the Optimal Method for Steroid Delivery in the Treatment of Chronic Rhinosinusitis With Nasal Polyps? - Hong, Seung-No; Kim, Dong-Young (Allergy, asthma & immunology research, 2019)
Chronic rhinosinusitis (CRS) is a prevalent heterogeneous inflammatory disorder of the sinonasal mucosa affecting up to 12.5% of the global population. Clinically, CRS can be classified as either CRS without nasal polyp (CRSsNP) or CRS with nasal polyp (CRSwNP). Steroids remain the mainstay treatment options in the management of type 2 inflammatory sinonasal disease and are considered a key component of medical therapy. The multifactorial anti-inflammatory effects along with the potent anti-remodeling effect of corticosteroids are the most important reasons for the widespread use in the treatment of CRSwNP. Currently, there are other considerable ongoing studies to find out the optimal method of corticosteroid delivery to sinonasal mucosa in CRSwNP. There are various intranasal steroid delivery devices available to physicians now.